The arts as a medium for care and self-care in dementia: arguments and evidence - Schneider, Justine M. (MDPI, 2018)
The growing prevalence of dementia, combined with an absence of effective pharmacological treatments, highlights the potential of psychosocial interventions to alleviate the effects of dementia and enhance quality of life. With reference to a manifesto from the researcher network Interdem, this paper shows how arts activities correspond to its definition of psycho-social care. It presents key dimensions that help to define different arts activities in this context, and illustrates the arts with reference to three major approaches that can be viewed online; visual art, music and dance. It goes on to discuss the features of each of these arts activities, and to present relevant evidence from systematic reviews on the arts in dementia in general. Developing the analysis into a template for differentiating arts interventions in dementia, the paper goes on to discuss implications for future research and for the uptake of the arts by people with dementia as a means to self-care.